Efektivitas Hukum Terhadap Realisasi Sistem Jaringan Sumber Daya Air pada Rencana Tata Ruang Wilayah Kota Tanjungpinang Periode 2014 – 2017 - Dzulkarnain, Dzulkarnain (Universitas Internasional Batam, 2019)
Development is a conscious effort made by humans to achieve a better life. The essence of development is how to make life better than today. On the other hand, major changes themselves are not fully achieved. In this case it could be due to the existence of unilateral interests, as the basis of this research is the Law of the Republic of Indonesia Number 26 of 2007 concerning Spatial Planning and the Presidential Regulation of the Republic of Indonesia Number 87 of 2011 concerning Spatial Planning for Batam, Bintan, and Karimun Areas. This research specifically explains how the Effectiveness Legal Theory analizes the implementation of the city spatial regulation. This study uses a socio-legal research. It finds that the settlement arrangement, spatial planning in the Regional Regulation Regarding the Regional Spatial Plan have been in consistent and harmony with the regional regulations concerning the Regional Spatial Plan and the agreement of the community and related offices. However, some of Tanjungpinang's urban space development policies are not in accordance with the policies of the regional regulation.